Intermolecular Mizoroki-Heck reaction of aliphatic olefins with high selectivity for substitution at the internal position - Lu, Yunpeng (2013)
New ligand for old reaction: The title reaction of aryltriflates with aliphatic olefins leads to substitution at the internal position with high selectivity. The ratio of the desired isomer (shown in the scheme) to the sum of all other isomers is generally above 10:1. The key to success is the use of a ferrocene bisphosphine ligand (R= 1-naphthyl). The reaction can be easily scaled up, and minor isomers can be separated by chromatography.